Recruitment of Gβγ controls the basal activity of G‐protein coupled inwardly rectifying potassium (GIRK) channels: crucial role of distal C terminus of GIRK1. (25th November 2014) - Kahanovitch, Uri; Tsemakhovich, Vladimir; Berlin, Shai; Rubinstein, Moran; Styr, Boaz; Castel, Ruth; Peleg, Sagit; Tabak, Galit; Dessauer, Carmen W.; Ivanina, Tatiana; Dascal, Nathan
<x xml:space="preserve">Abstract</x> Key points The G‐protein coupled inwardly rectifying potassium (GIRK) channel is an important mediator of neurotransmission via Gβγ subunit of the heterotrimeric Gi/o protein released by G‐protein coupled receptor (GPCR) activation. Channels containing the GIRK1 subunit exhibit high basal currents, whereas channels that are formed by the GIRK2 subunit have very low basal currents. GIRK1‐containing channels, but not channels consisting of GIRK2 only, recruit Gβγ to the plasma membrane. The Gα subunit of the G protein is not recruited by either GIRK1/2 or GIRK2. The unique distal C terminus of GIRK1 (G1‐dCT) endows the channel with strong interaction with Gβγ, and deletion of G1‐dCT abolishes the Gβγ recruitment and reduces the basal currents. These findings suggest that the basal activity of GIRK channels depends on channel‐induced recruitment of Gβγ. The unique C terminus of GIRK1 subunit plays an important role in Gβγ recruitment. Abstract The G‐protein coupled inwardly rectifying potassium (GIRK, or Kir3) channels are important mediators of inhibitory neurotransmission via activation of G‐protein coupled receptors (GPCRs). GIRK channels are tetramers comprising combinations of subunits (GIRK1–4), activated by direct binding of the Gβγ subunit of Gi/o proteins. Heterologously expressed GIRK1/2 exhibit high, Gβγ‐dependent basal currents (Ibasal) and a modest activation by GPCR or coexpressed Gβγ. Inversely, the GIRK2 homotetramers exhibit low Ibasal and strong activation by Gβγ. The high Ibasal of GIRK1 seems to be associated with its unique distal C terminus (G1‐dCT), which is not present in the other subunits. We investigated the role of G1‐dCT using electrophysiological and fluorescence assays in Xenopus laevis oocytes and protein interaction assays. We show that expression of GIRK1/2 increases the plasma membrane level of coexpressed Gβγ (a phenomenon we term 'Gβγ recruitment') but not of coexpressed Gαi3. All GIRK1‐containing channels, but not GIRK2 homomers, recruited Gβγ to the plasma membrane. In biochemical assays, truncation of G1‐dCT reduces the binding between the cytosolic parts of GIRK1 and Gβγ, but not Gαi3. Nevertheless, the truncation of G1‐dCT does not impair activation by Gβγ. In fluorescently labelled homotetrameric GIRK1 channels and in the heterotetrameric GIRK1/2 channel, the truncation of G1‐dCT abolishes Gβγ recruitment and decreases Ibasal. Thus, we conclude that G1‐dCT carries an essential role in Gβγ recruitment by GIRK1 and, consequently, in determining its high basal activity. Our results indicate that G1‐dCT is a crucial part of a Gβγ anchoring site of GIRK1‐containing channels, spatially and functionally distinct from the site of channel activation by Gβγ.